Factors Defining the Association Between Vitamin D and Testosterone in Males With Type 2 Diabetes and Hypogonadism - Hu, Xin; Han, Xue; Chen, Yu; Xiang, Pingping; Wei, Xiao; Gong, Tong; He, Zhiwei; Su, Yafeng; Chen, Guofang; Liu, Chao (Frontiers in Endocrinology, 2022)
Objective: This study aimed to evaluate serum 25(OH)D levels in diabetic men with and without hypogonadism, and figured out the potential factors influencing the connection between vitamin D and testosterone. Methods: A total of 367 men with type 2 diabetes mellitus (T2DM) were investigated, including 254 men with normal gonadal function (Group 1) and 113 men with hypogonadism (Group 2). Men with hypogonadism were classfied as either hypogonadotropic hypogonadism (Group 2a) or hypergonadotropic hypogonadism (Group 2b). Serum 25(OH)D levels were detected by liquid chromatography-tandem mass spectrometry in all cases. Morning testosterone, estradiol, dehydroepiandrosterone, prolactin, sex hormone-binding globulin, luteinizing hormone, follicle-stimulating hormone, thyroid function, parathyroid and adrenal hormones, fasting glucose, fasting insulin and hemoglobin A1c were also assessed. Results: The prevalence of hypovitaminosis D in men with T2DM was up to 96.46%. Serum 25(OH)D levels were significantly lower in men with hypogonadism than those with eugonadism (16.65±6.44 ng/mL vs. 18.17±6.17 ng/mL, P=0.033). The lowest 25(OH)D level was observed in Group 2a (16.22±6.52 ng/mL). After adjustment for the selected factors, serum 25(OH)D concentrations were shown to be favorably correlated with total testosterone concentrations (r=0.137, P=0.032). The relationship between 25(OH)D and testosterone was altered by age, duration, body mass index, and HbA1c. Serum 25(OH)D level was positively associated with total serum testosterone level in men with age <60 years (r=0.180, P=0.003), or with duration≥5 years (r=0.186, P=0.013), or with BMI≥28kg/m2 (r=0.431, P=0.000), or with HbA1c≥9% (r=0.145, P=0.031). Conclusions: These findings indicate that type 2 diabetes patients with hypogonadism have lower 25(OH)D levels than those without hypogonadism. There seems to be a positive association between the serum 25(OH)D and testosterone levels, which affected by age, duration, body mass index, and HbA1c .Vitamin D supplementation may be considered for patiens with T2DM and hypogonadism, especially for those with hypogonadotropic hypogonadism.